A Qualitative Study on the Impact of Sexual Assault and Its Approach to Cope with in Female Teenage Victims in Surakarta, Central Java - Nila Widya Keswara; Bhisma Murti; Argyo Demartoto (Journal of Health Promotion and Behavior, 2017)
Background: Studies have shown that sexual assault can lead to the profound impact on the victims. It may last short or long, and can even generate a "ripple effect" of negative symptoms in the affected workplace or living environment. This study aimed to explore the psychological and biological impacts of sexual assault and approach to cope with the trauma in female adolescent victims in Surakarta.Subjects and Method: This was a qualitative study conducted in Surakarta, Central Java. The informants were social workers working at Yayasan KAKAK, a non-government organization dealing with sexual harassment issues. The data were collected by in-depth interview. The informants provided information about psychological and biological impacts of sexual harassment as well as the approach to cope with the trauma in female adolescent victims in Surakarta.Results: The psychological impacts of sexual harassment included anger, fear, self-consciousness or embarrassment, difficulty sleeping, loss of appetite. According to the information provided by the informants, the victim’s life turned into a misery, and school became a place to be avoided. The sexual attacks led to feelings of demoralization and humiliation, causing loss of self-confidence and self-esteem. The victims were reported as having trouble studying or paying attention, less able to perform well, participating less, no longer going to study group, thinking about dropping a class or even leaving the school. Victims experienced symptoms such as headaches, stomach aches, nightmares and anxiety attacks. Yayasan KAKAK assisted victims by supporting and guiding about steps to be taken to protect victims and to cope with the aftermath.Conclusion: Sexual harassment has serious emotional and biological effects on adolescent victims. According to this research finding, one of the greatest mitigating factors to trauma is the acknowledgment that it is happening. Victims of sexual harassment should be assisted to find support and guidance about what steps can be taken to protect themselves and how to cope with the aftermath.Keywords: sexual harassment, female adolescent, copingCorrespondence: Nila Widya Keswara. Diploma Program in Midwifery, School of Health Polytechnics Dr. Soepraoen Hospital, Malang. Email: nilakeswara_purwanto@yahoo.com. Mobile: +6281235555056.https://doi.org/10.26911/thejhpb.2017.02.04.06